The nature of science in science curricula: methods and concepts of analysis - Ferreira, Sílvia (2022)
The article shows methods and concepts of analysis of the nature of science in science curricula through an exemplary study made in Portugal. The study analyses the extent to which the message transmitted by the Natural Science curriculum for Portuguese middle school considers the nature of science. It is epistemologically and sociologically grounded with particular emphasis on Bernstein’s theory of pedagogic discourse and Ziman’s conceptualization of science construction. The study used a mixed methodology and followed a dialectical process between the theoretical and the empirical. The results show that the nature of science has a low status in the curriculum with the exception of the external sociological dimension of science. Intra disciplinary relations between scientific and metascientific knowledge are mostly absent. Recontextualization processes occurred between the two main parts of the curriculum. These results are discussed and their consequences in terms of scientific learning are explored. The mode of analysis used in the study has the potential of highlighting the level of a science curriculum, in terms of specific aspects of the nature of science.